ANOTHER LIFE IS POSSIBLE: Black Fugitivity and Enclosed Places - SOJOYNER, DAMIEN M. (Cultural anthropology, 2017)
The Black fugitive in the United States has been a metaphorical and literal construction for both exposing oppressive forms of state governance and the development of strategic plans to achieve freedom from the state. Commonly thought of within a historical setting, the Black fugitive in this article is situated within the contemporary urban setting of Los Angeles, California. As told through the lived experience of young Black residents of the city, the narrative of fugitivity exposes the false promises of state governance, which is theorized as an enclosure. Specifically, this article focuses on self-removal from the state structure of formal education as a vehicle to understand Black fugitivity as a generative source of freedom from violent forms of state governance.